(untitled) (Biological Sciences - PJSIR, 2024)
Traditionally, potassium is applied in a single dose as a basal application on wheat crop which is unavailable to plants for later stages of growth due its luxury consumption by plants during initial stages of growth, adsorption to colloids, absorption by soil microbes and leaching loses. However, potassium application in an appropriate manner by altering its mode of application can greatly influence crop yield. Therefore, the experiment was conducted to study the impact of basal and split potassium application on yield and attributing traits of two wheat varieties at the experimental field of barley and Wheat Research Institute Tandojam, Pakistan during 2018-19. Two wheat varieties, namely TD-1 and Kiran-95 were sown in two factor randomized complete block design (main plot = varieties, sub plots = treatments) with three replications. The treatments were as follows: T1 = No K application, T2 = K application at 60 Kg K20/ ha at the time of sowing, T3 = K applications in two splits, i.e. 30 Kg K20/ha at sowing and 30 Kg K20/ha at tillering stage. The K application in two splits showed greater response as compared to basal application alone. In case of varieties, TD-1 performed well relatively in all parameters. Moreover, the highest number of tillers 12.13 per plants, number of grains 611.75 per plant, seed index (51.5), grain yield 2661.80 Kg/ha, straw yield 4503.30 Kg/ha, K content in grains (0.56%) and K content in straw (0.96%) was observed in split K application. For higher crop production therefore, K should be applied in two splits application.